Laser microdissection transcriptome data derived gene regulatory networks of developing rice endosperm revealed tissue- and stage-specific regulators modulating starch metabolism - Ishimaru, Tsutomu; Parween, Sabiha; Saito, Yuhi; Masumura, Takehiro; Kondo, Motohiko; Sreenivasulu, Nese (Springer, 2022)
Laser microdissection applied on the developing rice endosperm revealed tissue- and stage-specific regulators modulating programmed cell death and desiccation tolerance mechanisms in the central starchy endosperm following starch metabolism. Rice (Oryza sativa L.) filial seed tissues are heterozygous in its function, which accumulate distinct storage compounds spatially in starchy endosperm and aleurone. In this study, we identified the 18 tissue- and stage-specific gene co-regulons in the developing endosperm by isolating four fine tissues dorsal aleurone layer (AL), central starchy endosperm (CSE), dorsal starchy endosperm (DSE), and lateral starchy endosperm (LSE) at two developmental stages (7 days after flowering, DAF and 12DAF) using laser microdissection (LM) coupled with gene expression analysis of a 44 K microarray. The derived co-expression regulatory networks depict that distinct set of starch biosynthesis genes expressed preferentially at first in CSE at 7 DAF and extend its spatial expression to LSE and DSE by 12 DAF. Interestingly, along with the peak of starch metabolism we noticed accumulation of transcripts related to phospholipid and glycolipid metabolism in CSE during 12 DAF. The spatial distribution of starch accumulation in distinct zones of starchy endosperm contains specific transcriptional factors and hormonal-regulated genes. Genes related to programmed cell death (PCD) were specifically expressed in CSE at 12DAF, when starch accumulation was already completed in that tissue. The aleurone layer present in the outermost endosperm accumulates transcripts of lipid, tricarboxylic acid metabolism, several transporters, while starch metabolism and PCD is not pronounced. These regulatory cascades are likely to play a critical role in determining the positional fate of cells and offer novel insights into the molecular physiological mechanisms of endosperm development from early to middle storage phase.